2020
DOI: 10.1038/s41374-020-0436-1
|View full text |Cite
|
Sign up to set email alerts
|

A soluble endoplasmic reticulum factor as regenerative therapy for Wolfram syndrome

Abstract: Endoplasmic reticulum (ER) stress-mediated cell death is an emerging target for human chronic disorders, including neurodegeneration and diabetes. However, there is currently no treatment for preventing ER stress-mediated cell death. Here, we show that mesencephalic astrocyte-derived neurotrophic factor (MANF), a neurotrophic factor secreted from ER stressed cells, prevents ER stress-mediated β cell death and enhances β cell proliferation in cell and mouse models of Wolfram syndrome, a prototype of ER disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In addition to diabetes mellitus, cytoprotective effects of MANF have also been shown in animal models of Parkinson disease, ischemia, and retinal neurodegenerative diseases ( Airavaara et al., 2009 ; Glembotski et al., 2012 ; Lu et al., 2018 ; Neves et al., 2016 ; Voutilainen et al., 2009 ). Furthermore, we have recently reported that MANF prevents ER stress-mediated β-cell death in cell and mouse models of Wolfram syndrome ( Mahadevan et al., 2020 ). These previous reports and our findings indicate that screening assays, such as surface plasmon resonance (SPR), to discover small molecules that bind to NPTN and mediate survival and anti-inflammatory effects will lead to a novel therapeutic strategy for a variety of ER stress-related diseases, including diabetes, neurodegeneration, retinal degeneration, and Wolfram syndrome ( Abreu and Urano, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to diabetes mellitus, cytoprotective effects of MANF have also been shown in animal models of Parkinson disease, ischemia, and retinal neurodegenerative diseases ( Airavaara et al., 2009 ; Glembotski et al., 2012 ; Lu et al., 2018 ; Neves et al., 2016 ; Voutilainen et al., 2009 ). Furthermore, we have recently reported that MANF prevents ER stress-mediated β-cell death in cell and mouse models of Wolfram syndrome ( Mahadevan et al., 2020 ). These previous reports and our findings indicate that screening assays, such as surface plasmon resonance (SPR), to discover small molecules that bind to NPTN and mediate survival and anti-inflammatory effects will lead to a novel therapeutic strategy for a variety of ER stress-related diseases, including diabetes, neurodegeneration, retinal degeneration, and Wolfram syndrome ( Abreu and Urano, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MANF [81] no Stimulating proliferation and alleviating ER stress [81] Akt activators no Potentially inducing proliferation and survival by stimulating Akt pathway [80] Curr Opin Physiol. Author manuscript; available in PMC 2021 October 01.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, restoring Akt activity in WS may be a promising new avenue [24, 53,80]. Similarly, it has been reported that mesencephalic astrocyte-derived neurotrophic factor (MANF) can enhance the proliferation of remaining β cells in WS mice [81].…”
Section: Regenerative Medicinementioning
confidence: 99%
“…MANF is involved in protein homeostasis as it is upregulated upon ER stress, interacts with BiP and is secreted upon ER Ca 2+ depletion (Glembotski et al, 2012;Petrova et al, 2003). As MANF has pleiotropic actions in regulating ER homeostasis factors, including the UPR and Ca 2+ channels, it has been studied also extensively as a therapeutic approach for many ER stress related diseases, such as Wolfram disease, diabetes, stroke, hearing loss and Parkinson's disease (Airavaara et al, 2010;Airavaara et al, 2009;Albert and Airavaara, 2019;Glembotski et al, 2012;Herranen et al, 2020;Lindahl et al, 2014;Mahadevan et al, 2020;Voutilainen et al, 2015;Voutilainen et al, 2009).…”
Section: Downloaded Frommentioning
confidence: 99%